Structure and Stability of an Azoreductase with an FAD Cofactor from the Strict Anaerobe Clostridium perfringens - Morrison, Jessica; Dai, Shuo; Ren, Jie; Taylor, Amanda; Wilkerson, Mitchell; John, Gilbert; Xie, Aihua (Protein and Peptide Letters, 2014)
Azoreductase enzymes present in many microorganisms exhibit the ability to reduce azo dyes, an abundant industrial pollutant, to produce carcinogenic metabolites that threaten human health. All biochemically-characterized azoreductases, around 30 to date, have been isolated from aerobic bacteria, except for AzoC, the azoreductase of Clostridium perfringens, which is from a strictly anaerobic bacterium. AzoC is a recently biochemically-characterized azoreductase. The lack of structural information on AzoC hinders the mechanistic understanding of this enzyme. In this paper, we report on the biophysical characterization of the structure and thermal stability of AzoC by using a wide range of biophysical tools: Liquid Chromatography-Mass Spectrometry (LC-MS), Circular Dichroism Spectroscopy, Fouriertransform Infrared (FTIR) Spectroscopy, SDS-PAGE, Size Exclusion Chromatography, MALDI-TOF and UV-visible spectroscopy. We found that the flavin cofactor of AzoC is FAD, while all other structurally-known azoreductases employ FMN as a cofactor. The secondary structure of AzoC has 16% less α-helix structures, 5% more β-sheet structures and 11% more turn and unordered than the average of structurally-known azoreductase that have 10-14% sequence similarities with AzoC. We also found that oxidized AzoC is trimeric, which is unique amongst structurally known azoreductases. In contrast, reduced AzoC is monomeric, despite similarities in catalytic activity and thermal stability of oxidized and reduced AzoC. Our results show that the use of FTIR spectroscopy is crucial for characterization of the β-sheet content in AzoC, illustrating the need for complementary biophysical tools for secondary structural characterization of proteins.
Keywords: cofactor